The effect of cooperative learning on the speaking skill development for students of the first year of bachillerato at Jose Maria Velaz High School, in Huaquillas, during the 2015-2016 school year - Jaramillo Jara, Nelly Maribel (2016)
The goal of this research project was to enhance the speaking skill in the students of the first year of bachillerato at Jose Maria Velaz high school, located in Huaquillas city, during 2015-2016 school year, through the application of cooperative learning techniques. The study was engaged to thirty students divided into two groups, the first group was 15 students, which was called the control group where a pre-test was used and the second group was 15 students, which was called the experimental, a post-test was used too. The instrument for data collection was an oral test, which was tested by a rubric. The methodology was applied, descriptive and of field. The design was quantitative, quasi-experimental and transversal; these data were analyzed using statistical descriptive and inferential procedures. The research project showed that students' speaking skill was enhanced, by means of the Cooperative learning techniques. They learned how to work together and apply the components of communication properly